Lactulose and Melibiose Attenuate MPTP-Induced Parkinson’s Disease in Mice by Inhibition of Oxidative Stress, Reduction of Neuroinflammation and Up-Regulation of Autophagy - Lin, Chih-Hsin; Wei, Pei-Cih; Chen, Chiung-Mei; Huang, Yu-Ting; Lin, Jia-Lan; Lo, Yen-Shi; Lin, Jia-Li; Lin, Chung-Yin; Wu, Yih-Ru; Chang, Kuo-Hsuan; Lee-Chen, Guey-Jen (Frontiers in Aging Neuroscience, 2020)
Parkinson’s disease (PD) is a common neurodegenerative disease characterized by the progressive loss of dopaminergic (DAergic) neurons in the ventral brain. A disaccharide trehalose has demonstrated the potential to mitigate the DAergic loss in disease models for PD. However, trehalose is rapidly hydrolyzed into glucose by trehalase in the intestine, limiting its potential for clinical practice. Here, we investigated the neuroprotective potential of two trehalase-indigestible analogs, lactulose and melibiose, in sub-chronic 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced mouse model of PD. Treatment with MPTP generated significant motor deficits, inhibited dopamine levels, and down-regulated dopamine transporter (DAT) in the striatum. Expression levels of genes involved in anti-oxidative stress pathways, including superoxide dismutase 2 (SOD2), nuclear factor erythroid 2-related factor 2 (NRF2), and NAD(P)H dehydrogenase (NQO1) were also down-regulated. Meanwhile, expression of the oxidative stress marker 4-hydroxynonenal (4-HNE) was up-regulated along with increased microglia and astrocyte reactivity in the ventral midbrain following MPTP treatment. MPTP also reduced the activity of autophagy, evaluated by the autophagosomal marker microtubule-associated protein 1 light chain 3 (LC3)-II. Lactulose and melibiose significantly rescued motor deficits, increased dopamine in the striatum, reduced microglia and astrocyte reactivity as well as decreased levels of 4-HNE. Furthermore, lactulose and melibiose up-regulated SOD2, NRF2, and NQO1 levels, as well as enhanced the LC3-II/LC3-I ratio in the ventral midbrain with MPTP treatment. Our findings indicate the potential of lactulose and melibiose to protect DAergic neurons in PD.